Adaptation and Validation of the Self-Efficacy Questionnaire for Children (SEQ-C) for Indonesian Orphanage Students - Ghozali Rusyid Affandi; Widyastuti Widyastuti; Mohammad Faizal Amir (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to adapt the Self-Efficay Questionnaire for Children (SEQ-C) into Indonesian and analyze the quality of its psychometric properties. The adaptation model refers to the concept developed by Beaton with 5 (five) stages, including initial translation, synthesis of the translations, back translation, expert committee, and pre-final version testing. This research method used descriptive quantitative by adapting measuring instruments. This research was conducted offline and online on students who live in the Aisyiyah Orphanage in East Java and students who are cared for by their parents with an age range of 12-18 years (N = 187; Boys 16% and Girls 83%). This study used Self-Efficacy Questionnaire for Children (SEQ-C) instruments with data collection techniques using the SEQ-C scale. Data analysis using confirmatory factor analysis (CFA) and internal consistency reliability using JASP Version 16.0.0. The results of the CFA in model 2 show that there is a model fit (model fit) with the data, with a score of 2 = 169,999 (p = 0.421 > 0.05); RMSEA = 0.008 < 0.08; CFI = 0.999 > 0.9; TLI = 0.999 > 0.9; SRMR = 0.059 < 0.08 and has a loading factor > 0.4. Reliability test using internal consistency on each factor SEQ-C shows good results (including factors A, B, and C). SEQ-C, adapted into Indonesian, has met adequate validity and reliability to be used as a measuring tool for self-efficacy in students living in orphanages in Indonesia. However, it needs to be tested on students more generally, starting from elementary to high school.